Simplifying Java 8 with Lambdas - Warburton, Richard (Computer technologist) (O'Reilly Media, 2014)
"In this webcast we go through a series of code examples, that show how to: use the new lambda expressions feature, write more readable and faster collections processing code using the Streams API, build complex data processing systems with the new collector abstraction, use Lambda expressions in your own code."--Resource description page.